Otomatisasi Pengatur pH dan Nutrisi pada Tanaman Hidroponik Berbasis Internet of Things di Aswana Hidroponik - Joyopranoto, Vincensius Agung Wibowo; Baraga, Bernaditus Yordan; Rahardjo, Mikha El Charisto; Mahendra, Christy; Lianawati, Yosita (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
This study discusses the design of an automated pH and nutrient control system for hydroponic plants based on the Internet of Things (IoT). The objective of this study to develop a system capable of reading solution conditions and sending data in real time through an IoT platform to facilitate monitoring without manual intervention. The system is designed using an ESP32 microcontroller as the control center, a pH sensor, a TDS meter sensor, and a peristaltic pump for the solution injection process. The sensor reading data is sent to the IoT server using the Blynk platform. The test results show that system is capable of sending valid and consistent pH and TDS data to the Blynk dashboard with an accuracy level ±98%, making it easier for users to monitor the condition of the nutrient solution remotely. This research is the first step towards an efficient and integrated automatic hydroponic control system.